Neonatal High Bone Mass With First Mutation of the NF‐κB Complex: Heterozygous De Novo Missense (p.Asp512Ser) RELA (Rela/p65). (6th August 2015) - Frederiksen, Anja L; Larsen, Martin J; Brusgaard, Klaus; Novack, Deborah V; Knudsen, Peter Juel Thiis; Schrøder, Henrik Daa; Qiu, Weimin; Eckhardt, Christina; McAlister, William H; Kassem, Moustapha; Mumm, Steven; Frost, Morten; et al.
ABSTRACT: Heritable disorders that feature high bone mass (HBM) are rare. The etiology is typically a mutation(s) within a gene that regulates the differentiation and function of osteoblasts (OBs) or osteoclasts (OCs). Nevertheless, the molecular basis is unknown for approximately one‐fifth of such entities. NF‐κB signaling is a key regulator of bone remodeling and acts by enhancing OC survival while impairing OB maturation and function. The NF‐κB transcription complex comprises five subunits. In mice, deletion of the p50 and p52 subunits together causes osteopetrosis (OPT). In humans, however, mutations within the genes that encode the NF‐κB complex, including the Rela/p65 subunit, have not been reported. We describe a neonate who died suddenly and unexpectedly and was found at postmortem to have HBM documented radiographically and by skeletal histopathology. Serum was not available for study. Radiographic changes resembled malignant OPT, but histopathological investigation showed morphologically normal OCs and evidence of intact bone resorption excluding OPT. Furthermore, mutation analysis was negative for eight genes associated with OPT or HBM. Instead, accelerated bone formation appeared to account for the HBM. Subsequently, trio‐based whole exome sequencing revealed a heterozygous de novo missense mutation (c.1534_1535delinsAG, p.Asp512Ser) in exon 11 of RELA encoding Rela/p65. The mutation was then verified using bidirectional Sanger sequencing. Lipopolysaccharide stimulation of patient fibroblasts elicited impaired NF‐κB responses compared with healthy control fibroblasts. Five unrelated patients with unexplained HBM did not show a RELA defect. Ours is apparently the first report of a mutation within the NF‐κB complex in humans. The missense change is associated with neonatal osteosclerosis from in utero increased OB function rather than failed OC action. These findings demonstrate the importance of the Rela/p65 subunit within the NF‐κB pathway for human skeletal homeostasis and represent a new genetic cause of HBM. © 2015 American Society for Bone and Mineral Research.